Analisis Komparatif Model Dialektika Pos-Islamisme di Dunia Islam antara Arab Saudi dan Iran (State Islamic Institute of Kudus (IAIN Kudus), 2023)
This study aims to analyze the relationship between Islam and the state in Saudi Arabia and Iran, using the approach of post-Islamism. Post-Islamism is a concept that refers to the shift of Islamist groups towards modernity and democracy. It was first introduced by Iranian intellectual, Asef Bayat, in the 1990s. Since then, it has been used to analyze the phenomenon of political Islam in different countries, especially after the Cold War. In Saudi Arabia, changes have occurred since Mohammed bin Salman was appointed as crown prince in 2016. In Iran, civil society actions, such as the 2022 death of Mahsa Amini, have driven the change. The research problem is to compare the post-Islamism model that occurs in Saudi Arabia and Iran. The comparative case study method with library research techniques was used. The research findings show that the pattern of post-Islamism in Saudi Arabia differs from that of Iran. In Saudi Arabia, post-Islamism is top-down, starting from state politics without civic movement. However, Iran illustrates the opposite - it is bottom-up and initiated by civil society against the state.